Essential oil of Syzygium aromaticum reverses the deficits of stress-induced behaviors and hippocampal p-ERK/p-CREB/brain-derived neurotrophic factor expression - Liu, Bin-Bin; Luo, Liu; Liu, Xiao-Long; Geng, Di; Li, Cheng-Fu; Chen, Shao-Mei; Chen, Xue-Mei; Yi, Li-Tao; Liu, Qing (Planta medica, 2015)
Syzygium aromaticum has been widely used in traditional medicine. Our study investigated the safety and antidepressant-like effects of the essential oil of S. aromaticum after acute or long-term treatment. Using GC-MS, a total of eight volatile constituents were identified in the essential oil of S. aromaticum. The single LD50 was approximately 4500 mg/kg based on a 24-h acute oral toxicity study. In a long-term repeated toxicity study of this essential oil (100, 200, and 400 mg/kg, p. o.), only 400 mg/kg induced a significant decrease in body weight. In addition, no significant changes in relative organ weights and histopathological analysis were observed in all doses of essential oil-treated mice compared with the control group. Furthermore, acute S. aromaticum essential oil administration by gavage exerted antidepressant-like effects in the forced swimming test (200 mg/kg, p < 0.05) and tail suspension test (100 and 200 mg/kg, p < 0.05). Long-term S. aromaticum essential oil treatment via gavage significantly increased sucrose preference (50 mg/kg, p < 0.05; 100 and 200 mg/kg, p < 0.01) as well as elevated the protein levels of hippocampal p-ERK, p-CREB, and brain-derived neurotrophic factor in mice exposed to chronic unpredictable mild stress. These results confirmed the safety of the essential oil of S. aromaticum and suggested that its potent antidepressant-like property might be attributed to the improvement in the hippocampal pERK1/2-pCREB-BDNF pathway in rats exposed to chronic unpredictable mild stress.